2021
DOI: 10.1038/s41598-021-81916-y
|View full text |Cite
|
Sign up to set email alerts
|

Human amnion-derived mesenchymal stem cells attenuate xenogeneic graft-versus-host disease by preventing T cell activation and proliferation

Abstract: Acute graft-versus-host disease (GVHD) is characterized by severe tissue damage that is a life-threatening complication of allogeneic hematopoietic stem cell transplantation. Due to their immunosuppressive properties, mesenchymal stem cells (MSC) have been increasingly examined for the treatment of immune-related diseases. We aimed to assess the immunosuppressive effects of human amnion-derived MSC (AMSC) in a xenogeneic GVHD NOD/Shi-scid IL2rγnull mouse model using human peripheral blood mononuclear cells (PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(41 reference statements)
1
8
1
Order By: Relevance
“…They also compared the immunomodulatory effects of AMSCs and BM-MSCs in vitro, and found that both AMSCs and BM-MSCs reduced the concentration of TNF-α and IFN-γ expressed by PBMCs. 48 However, this study did not detect T cell and inflammatory cytokine levels in the target organs of aGVHD mice. We examined CD3+CD4+ T and CD3+CD8+ T cells in the main target organs of our aGVHD mice, and found a significant decrease in the proportion of CD3+CD4+ T and CD3+CD8+ T cells in these tissues of mice treated with hAMSCs compared to control group.…”
Section: Discussioncontrasting
confidence: 59%
“…They also compared the immunomodulatory effects of AMSCs and BM-MSCs in vitro, and found that both AMSCs and BM-MSCs reduced the concentration of TNF-α and IFN-γ expressed by PBMCs. 48 However, this study did not detect T cell and inflammatory cytokine levels in the target organs of aGVHD mice. We examined CD3+CD4+ T and CD3+CD8+ T cells in the main target organs of our aGVHD mice, and found a significant decrease in the proportion of CD3+CD4+ T and CD3+CD8+ T cells in these tissues of mice treated with hAMSCs compared to control group.…”
Section: Discussioncontrasting
confidence: 59%
“…Solid black arrows indicate GvHD pathology, including high infiltration of mononuclear cells in hepatic and lung tissues, shortening and/or structural abnormality of intestinal villi, and bronchial luminal narrowing. [55][56][57][58][59] The corresponding number at each scale bar indicates an image size (mm). was demonstrated in a previous study, 68 suggesting the feasibility of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Histopathology of intestine, liver, and lung tissues obtained from all groups. Solid black arrows indicate GvHD pathology, including high infiltration of mononuclear cells in hepatic and lung tissues, shortening and/or structural abnormality of intestinal villi, and bronchial luminal narrowing [55][56][57][58][59]. The corresponding number at each scale bar indicates an image size (mm).…”
mentioning
confidence: 99%
“…A recent study showed that AMSCs reduced the activity of human CD8 + T cells and TNF-α in the peripheral blood of xeno-GVHD mice. They also compared the immunomodulatory effects of AMSCs and BM-MSCs in vitro, and found that both AMSCs and BM-MSCs reduced the concentration of TNF-α and IFN-γ expressed by PBMCs [35]. However, this study did not detect T cell and in ammatory cytokine levels in the target organs of aGVHD mice.…”
Section: Discussionmentioning
confidence: 73%